Experiencia de trabajo docente, análisis de caso en la unidad educativa intercultural bilingüe Ing. Hermel Ayupanda del cantón Colta - Pucha Lema, Jorge (2016)
This qualitative research was conducted with teachers of the Education Unit Ayupanda Hermel. The main objective of this research was to collect the voice from those who build in everyday classroom teaching skills from practice. Thus, this research work includes stories of teachers on their own experience. For this was chosen as the instrument depth interviews; in this way the work was built through dialogue between practicing teachers and teachers who will start his career. The importance of this research is that it gives us information about the professional life, recognizing what teachers know and they know from their own practice and work several years in the educational field.